Siyaha Tourism Application Development: E-Encyclopedia of Arabic Tourism in Malang, East Java, Indonesia - R. Taufiqurrochman; Agung Prasetiyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The trend growth of travelers abroad from the Middle East, especially from Saudi Arabia, is getting increased. In the year 2019, Indonesia managed to reach rank first tour halal popular world. In the digital era, these things must of course be balanced with a marketing communication strategy that demands an Arabic travel e-encyclopedia. The Siyaha Tourism application developed by researchers is one of the right alternatives. This application is designed and developed using research and development (RD) with a Four-D model combined with the procedure for compiling an encyclopedia based on Arabic lexicography. The combination of the media application development process and the preparation of this encyclopedia is a good outcome with complete product specifications, both in terms of content and features. The results of the validation from language, tourism, and culture experts also show that the Siyaha Tourism application in the form of android for mobile and the website www.siyaha.online is worthy of being a media for tourism information, especially tourist destinations in Malang City, East Java, Indonesia which the government has designated as city pilot project of the halal tourism program. 212 respondents rated this product. The results show that the quality of the Siyaha Tourism application is good and needed for tourism.